RANCANG BANGUN SISTEM PENGENALAN WAJAH DAFTAR PENCARIAN ORANG (DPO) BERBASIS JARINGAN SARAF TIRUAN - Hendro FJ Lami; Silvester Tena; Beby H.A. Manafe; Johanis F.M Bowakh; Nursalim Nursalim; Sudirman S (Universitas Nusa Cendana, 2019)
This study aims to design a system that is able to recognize the face of a people search list (DPO). The application is built using opencv and dlib ddan system testing is done with a dataset consisting of 6 target people. The target was identified when it was exactly perpendicular to the camera but the detection failed when the target's face was not exactly perpendicular. This study also models the transmission of target data detected using long range radio (LORA) at a frequency of 915